Quantitative three-dimensional nondestructive imaging of whole anaerobic ammonium-oxidizing bacteria - Peng, Meng-Wen (J Synchrotron Radiat, 2020)
Anaerobic ammonium-oxidizing (anammox) bacteria play a key role in the global nitrogen cycle and in nitrogenous wastewater treatment. The anammox bacteria ultrastructure is unique and distinctly different from that of other prokaryotic cells. The morphological structure of an organism is related to its function; however, research on the ultrastructure of intact anammox bacteria is lacking. In this study, in situ three-dimensional nondestructive ultrastructure imaging of a whole anammox cell was performed using synchrotron soft X-ray tomography (SXT) and the total variation-based simultaneous algebraic reconstruction technique (TV-SART). Statistical and quantitative analyses of the intact anammox bacteria were performed. High soft X-ray absorption composition inside anammoxosome was detected and verified to be relevant to iron-binding protein. On this basis, the shape adaptation of the anammox bacteria response to iron was explored.